Medium-induced modification of azimuthal correlations of electrons from heavy-flavor hadron decays with charged particles in Pb-Pb collisions at √sNN=5.02 TeV - Abualrob, I. J.; Acharya, S.; Rinella, G. Aglieri; Aglietta, L.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahuja, I.; Akbar, Z.; Akindinov, A.; Akishina, V.; et al. (SPRINGER, 2026)
The azimuthal-correlation distributions between electrons from the decays of heavy-flavor hadrons and associated charged particles in Pb-Pb collisions at root s(NN) = 5.02 TeV are reported for the 0-10% and 30-50% centrality classes. This measurement provides access to the jet-like correlation observables in the heavy-flavor sector in Pb-Pb collisions. The analysis is performed for trigger electrons from heavy-flavor hadron decays with transverse momentum 4 4 GeV/c on the away side. The I-AA for electron triggers from heavy-flavor hadron decays is compared with that for light-flavor and strange-particle triggers to investigate the dependence on different fragmentation processes and parton-medium dynamics, and is found to be the same within uncertainties.
Keywords: NUCLEAR MODIFICATION FACTOR; QUARK-GLUON PLASMA; ANGULAR-CORRELATIONS; ENERGY-LOSS; MESONS; QCD; PP; PERSPECTIVE; Physics